A molecular dynamics investigation of the atomic structural behavior of the interaction between amyloid beta protein and Aspirin within an aqueous nanodomain - Le, Quynh Hoang; Heydaripour, Shokoufeh; Farhadi, Bita; Rashid, Rzgar Farooq; İnç, Mustafa (Elsevier Sci Ltd, 2023)
Alzheimer's disease is a neurodegenerative disorder whose symptoms include cognitive problems such as learning and memory deficits. Suffering from this disease is considered one of the most important causes of forgetfulness, as more than half of the people with dementia in old age have this disease. Inside the scope of the present investigation, we explain this protein's atomic behavior interaction with Aspirin in the water system. At the same time, it is contained within a metallic nanochannel (Cu nanochannel). In order to accomplish this goal, the Molecular Dynamics (MD) technique was used when the circumstances were in equilibrium. In addition, the atomic behavior of the Amyloid beta interaction with Aspirin was characterized by the calculation of physical parameters such as temperature, potential energy, RDF, density/temperature/ velocity characteristics, and peptide volume. The MD simulation results showed that the protein's atomic structure was stable in water system when placed within Cu nanochannels. After a time interval oft = 10 nanoseconds, the value of the volume of the Amyloid beta protein shifts from 40,054.1 angstrom 3 to 69,178.8 angstrom 3. Additionally, the highest velocity and density/ temperature characteristics, exceed 17.73 angstrom/fs, 0.1426 atoms/angstrom 3, and 1451.33 K, respectively.
Keywords: Molecular dynamics; Amyloid beta; Aspirin; Velocity; Nanochannels